(untitled) (Proceedings of International Educators Conference, 2023)
Nowadays, biophysics is an important component of the modern professional activity of the whole society, but also of every doctor, especially it is related to science and innovative technology within the framework of medical education. In the development of science and technology, which is achieving effective results in the world, the science of biophysics is not similar to any processes in non-living nature and takes place in unique conditions.